Partial oxidation of methane with hydrogen peroxide over Fe-ZSM-5 catalyst - Kim, Min Sik; Park, Ki Hun; Cho, Sung June; Park, Eun Duck (Catalysis Today, 2021)
The effect of the catalyst preparation method on the catalytic activity of Fe-ZSM-5 for the partial oxidation of methane with H2O2 in an aqueous phase was examined. UV–vis spectroscopy and FT-IR spectroscopy after NO adsorption were used to characterize the prepared catalysts. Various preparation methods, including wet impregnation, solid-state ion-exchange, chemical vapor impregnation, hydrothermal synthesis, and aqueous phase ion-exchange were compared. Among them, the aqueous phase ion-exchange method demonstrated the best results in producing isolated or oligonuclear extra-framework Fe species, which showed the highest catalytic activity. On the other hand, bulk iron oxides did not decompose H2O2 nor did they activate methane. The total product yield and the amount of H2O2 consumed increased with increasing Fe content in the case of the Fe-ZSM-5 catalyst prepared using an ion-exchange method. However, the fraction of less active Fe species, such as iron oxide clusters and larger iron oxide aggregates on the external crystal surface, increased with the Fe content, resulting in a decrease in the total product yield per Fe content and the amount of H2O2 consumed per Fe content.
Keywords: Catalyst preparation methods; Fe-ZSM-5 catalysts; FTIR spectroscopy; Ion-exchange methods; Iron oxide cluster; Partial oxidation of methane; Preparation method; Solid state ion exchange; Fe-ZSM-5; Formic acid; Hydrogen peroxide; Methane oxygenates; Partial oxidation of methane; Preparation method